Academic stress in adolescents: findings from a school-based study in Belagavi district - Haritay, Shivani; Angolkar, Mubashir; Koparde, Vinayak; Oswal, Deshna; Carvalho, Alex (Frontiers in Public Health, 2025)
BackgroundAcademic stress has emerged as a significant risk factor for mental health development during adolescence. Schools have a considerable influence on adolescents’ development, but increasing academic pressures and social expectations have caused students to experience higher levels of stress, impacting their mental health and overall development.ObjectiveTo assess academic stress levels and the factors associated with it among students aged 13–15 years in Belagavi district, Karnataka.MethodsA school-based survey was conducted among 1,426 students from four CBSE schools using universal sampling. Data were collected from July to September 2023. The Educational Stress Scale for Adolescents (ESSA) was used to measure academic stress. Statistical analysis involved Chi-square tests, Fisher’s exact test, and independent t-tests.ResultsAmong the 1,426 students, 74% reported high levels of academic stress, with 17% reporting medium levels. Academic stress levels were significantly associated with age (p = 0.027), area (p = 0.000), father’s education (p = 0.023), and gender (p = 0.001). Male students experienced significantly higher stress levels in study pressure, grade-related anxiety, self-expectation, and self-despondency (p < 0.05). Female students experienced slightly higher stress related to workload, though this was not statistically significant.ConclusionAcademic stress is prevalent among students and is significantly influenced by various sociodemographic variables.